2006
DOI: 10.1021/jp056650c
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Solvent and Rotational Relaxation of Glycerol in the Nanocavity of Reverse Micelles

Abstract: The dynamics of solvent and rotational relaxation of Coumarin 480 and Coumarin 490 in glycerol containing bis-2-ethyl hexyl sulfosuccinate sodium salt (AOT) reverse micelles have been investigated with steady-state and time-resolved fluorescence spectroscopy. We observed slower solvent relaxation of glycerol confined in the nanocavity of AOT reverse micelles compared to that in pure glycerol. However, the slowing down in the solvation time on going from neat glycerol to glycerol confined reverse micelles is no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
51
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(58 citation statements)
references
References 103 publications
7
51
0
Order By: Relevance
“…With deep-UVe xcitation, also ah igher lying electronic state is reached, but the emission spectra in Figure 1b impart relaxation to the lowest lying excited state for both UV wavelengths. [80,81] The value of t 2 = 204 ps found for PTCi ng lycerol might correspond to these observations. The involvement of solvation can be inferred from the TCSPC data in the viscouss olvents ethylene glycol and glycerolw here af urther component (t 2 in Ta ble 1) had to be included for satisfactorily fitting the data.…”
Section: Relaxation (Decay Times T 2 and T 3 )supporting
confidence: 67%
See 1 more Smart Citation
“…With deep-UVe xcitation, also ah igher lying electronic state is reached, but the emission spectra in Figure 1b impart relaxation to the lowest lying excited state for both UV wavelengths. [80,81] The value of t 2 = 204 ps found for PTCi ng lycerol might correspond to these observations. The involvement of solvation can be inferred from the TCSPC data in the viscouss olvents ethylene glycol and glycerolw here af urther component (t 2 in Ta ble 1) had to be included for satisfactorily fitting the data.…”
Section: Relaxation (Decay Times T 2 and T 3 )supporting
confidence: 67%
“…The average solvation time of glycerol determined with various coumarin dyes is on the order of several hundred picoseconds with the exact value depending on the solute. [80,81] The value of t 2 = 204 ps found for PTCi ng lycerol might correspond to these observations.…”
Section: Relaxation (Decay Times T 2 and T 3 )supporting
confidence: 67%
“…The slow relaxation of GLY molecules within neat GLY makes the entire solvation time much slower (B500-1000 ps) compared to the bulk water (Bfew ps). [35][36][37] In contrast to the GLY, DMSO is known as a fast solvent. The typical solvation time within this solvent is only B3 ps.…”
Section: Steady State Spectra and Time Resolved Fluorescence Stokes S...mentioning
confidence: 99%
“…10 In addition, Seth and co-workers published a series of reports on solvent and rotational relaxation of coumarin fluorescence probes in various IL-containing microemulsions or micellar solutions. 29,30 The self-assembled structures of surfactants with ILs have shown different advantages over the traditional ones notably in the preparation of nanostructures. A recent study has shown that IL-based microemulsions can be used to produce polymer nanoparticles, gels, and open-cell porous materials.…”
Section: Introductionmentioning
confidence: 99%